2014
DOI: 10.2340/00015555-1841
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology of Hidradenitis Suppurativa – Which Antibiotics are the Treatment of Choice?

Abstract: The bacterial superinfection in hidradenitis suppurativa (HS), although it does not initiate the disease itself, seems to be one of the major contributors to an inflammatory vicious circle. Antibiotic therapy is therefore commonly prescribed in HS. This study was undertaken to evaluate the prescription of systemic antibiotics in the light of bacteriological cultures and antibiograms. The study was conducted on a group of 69 patients with HS. The huge majority (n=62) of the patients were treated with antibiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
63
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 29 publications
3
63
1
1
Order By: Relevance
“…Furthermore, they can inhibit angiogenesis [35], which is a common process in HS inflammation. Because of these anti-inflammatory properties and a mild side-effect profile, tetracyclines are useful for longterm treatment and stabilization of HS [29,33]. However, they are less effective in treating or preventing exacerbations of HS.…”
Section: Tetracyclinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they can inhibit angiogenesis [35], which is a common process in HS inflammation. Because of these anti-inflammatory properties and a mild side-effect profile, tetracyclines are useful for longterm treatment and stabilization of HS [29,33]. However, they are less effective in treating or preventing exacerbations of HS.…”
Section: Tetracyclinesmentioning
confidence: 99%
“…However, they are less effective in treating or preventing exacerbations of HS. Matusiak et al [29] cultured the bacteria isolated from HS patients and found that 64 % of the isolated strains were resistant for tetracyclines. In addition, in a randomized double-blind controlled trial, topical clindamycin 1 % lotion was shown to be as effective as systemic tetracycline 500 mg twice daily in terms of number of nodules and abscesses and patient pain score [37].…”
Section: Tetracyclinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, autosomal dominant hyper-IgE syndrome patients have deficient Th17 response and are at increased risk for SSSI but not for disseminated S. aureus infection (25). Furthermore, patients with acne inversa have deficits in cutaneous interleukin-22 (IL-22) responses and exhibit staphylococcal persistence in skin abscesses (26,27). These patterns suggest that innate and adaptive immune responses must cooperate for optimal host defense against MRSA.…”
mentioning
confidence: 99%
“…In comparison, because they have a defective Th17 response, patients with Job's syndrome (hyper-IgE syndrome) and atopic dermatitis are at increased risk of SSSI, but typically less so for systemic S. aureus infection (34)(35)(36). Further, patients with acne inversa exhibit staphylococcal persistence in skin abscesses due to deficiencies in the cutaneous interleukin-22 (IL-22) response (37,38). Thus, different aspects of the host immune system are required to defend cutaneous versus hematogenous compartments against S. aureus infection.…”
mentioning
confidence: 99%